Pengaruh Metode Show And Tell dan Sikap Terhadap Peningkatan Kompetensi Bicara Bahasa Indonesia Pada Siswa Kelas III di UPTD SDN 3 Parseh Socah - Susila, Betty; Wahyuningtyas, Sri; Sunardjo, Sunardjo (Penerbit STKIP PGRI Bangkalan, 2024)
A review of observations conducted on March 1, 2023, revealed that students in the third grade at SDN Parseh 3 Socah Bangkalan exhibited suboptimal proficiency in oral communication. This conclusion was reached through interviews with teachers. Potential method for enhancing speaking competence is the show-and-tell approach. The objective of this research is to ascertain whether there is a discernible difference in the interaction effect between the utilisation of the Show and Tell method and Attitude towards Speaking Competence. This study employs a quantitative approach and presents its findings in the form of descriptive statistics accompanied by graphical representations (Ibnu Hajar, 2000; 30). The output of the analysis of variance (ANOVA) yielded a Fhitung value of 52.893 with a significance level of 0.000. The ANOVA table indicates that the value of the numerator (df) is 2 and the value of the denominator (db) is 15. Consequently, the Ftable value is 3.680 for the 5% level. From Table 4.16, it can be seen that the significance level (Sig.) is 0.000, which is less than 0.05. The value of the Fhitung is 52.893, which is greater than the Ftable value of 3.680. This indicates that the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. This implies that there is an effect of the show-and-tell method and student attitudes on speaking skills. This method accounts for an 84.2% influence on mathematics learning outcomes, with the remaining 15.8% influenced by variables outside the scope of the show-and-tell method and student attitudes